Social prescribing: a 'natural' community-based solution. (2nd June 2020) - Howarth, Michelle; Griffiths, Alistair; da Silva, Anna; Green, Richard
Abstract : This paper discusses social prescribing as part of the wider NHS England universal personalised care model, and it describes how community nurses can engage with social prescribing systems to support community resilience. A case study based on the example of gardening, as a nature-based social prescription provided by the RHS Bridgewater Wellbeing Garden, is provided to illustrate the scope, reach and impact of non-medical, salutogenic approaches for community practitioners. The authors argue that social prescribing and, in particular, nature-based solutions, such as gardening, can be used as a non-medical asset-based approach by all health professionals working in the community as a way to promote health and wellbeing. They consider how the negative impact of social distancing resulting from COVID-19 restrictions could be diluted through collaboration between a holistic, social prescribing system and community staff. The paper presents a unique perspective on how community nurses can collaborate with link workers through social prescribing to help combat social isolation and anxiety and support resilience.